Short-term fiscal imbalance comparison in V4 countries using a dynamic conditional correlation approach - Mihóková, Lucia; Martinková, Slavomíra; Dráb, Radovan (Equilibrium. Quarterly Journal of Economics and Economic Policy, 2017)
Research background: The crisis periods have highlighted the interdependence between individual European economies in the area of economic and fiscal development. The common development tendencies raise the question whether the fiscal indebtedness and preferred fiscal policy of V4 countries can be considered as interdepending. Considering this assumption, a possibility for implementing a similar type of consolidation in selected clusters of countries could be proposed. Purpose of the article: The research is, from the empirical point of view, focused on the analysis and comparison of primary balance indicator, analysis and assessment of fiscal measures (in identified fiscal episodes) and analysis of fiscal development intercorrelations using the dynamic conditional correlation approach. Methods: The empirical assessment of the research objective is, from the methodological point of view, divided into five phases: (1) the calculation of primary deficit indicator, (2) the analysis, comparison and assessment of the fiscal development in the V4 countries based on the annual primary deficit during the selected period 1999?2016, (3) the seasonal adjustment of performing time series and non-stationarity testing, (4) the dynamic conditional correlation approach (DCC) application. Within the analysis, the traditional and specific methods were used (time series analysis, content analysis, descriptive statistics, correlation methods, DCC approach). Findings & Value added: The results of the research suggest that between V4 countries do exist significant differences based on which cannot be clearly confirmed the assumption about the fiscal development interdependence in V4 countries. From the long-term perspective, it can be stated that the fiscal development in V4 countries is a very slightly positively related aspect, but in the context of the implementation of a common consolidation strategy it is not sufficient.